Economics of White Maize Production in Fufore Local Government Area of Adamawa State, Nigeria - U.M. Bakari and Musa Hamman, Jalaludeen Usman, Jimjel Zalkuwi, (International Journal of Scientific Research and Management (IJSRM), 2015)
The research work was undertaken to examine the Economics of White Maize production in Fufore LGA of Adamawa State. Primary data were collected from 110 White Maize Farmers, using multi-stage sampling techniques. Descriptive Statistics, Gross Margin, Regression analysis as well as Marginal Value Product were used in the analysis of data collected with the aid of well structured Questionnaires. Majority of the respondents were young Married Men who are educated and acquire their land through renting (82.73%, 59.09%, 70.91%, 81.82% and 54.55%) respectively. The result of the average gross and net farm income per hectare of N52, 118.03 and N49, 116.53 respectively, revealed that white maize production is profitable venture in the study area. The linear production Function revealed that 91.2% of the total variation in the output of white maize was accounted by variables input (age, fertilizer, farming experience and seed) that were statistically significance at 5 and 10% level respectively and positively affect the output of white Maize. The Marginal value product (MVP) analysis indicates that seed and fertilizer were Under Utilized; therefore increase in these inputs would increase the output of white Maize. Shortage/high cost of input, shortage of labour as well as Clashes with pastoralists were the major problems faced by white Maize farmers in the study area. The study therefore, recommends among others that farmers should be educated on the ne ed to associate with one another to avoid unnecessary conflicts between them and herdsmen in the study area.